El rol del maestro en la educación para la sostenibilidad ambiental. - Canto, Enma M. (2022)
The objective of this work is to establish the role that the teacher fulfills in environmental education, taking into account the actions of caring for nature that he carries out inside and outside the classroom, for the strengthening of environmental sustainability; The research presents a theoretical foundation with several themes such as: Sustainable Development, Sustainable Pedagogy, Environmental Education, Teacher's Role in Sustainable Pedagogy, pollution, government and educational actions to develop for environmental sustainability. In the execution of the study, a methodology based on a qualitative and quantitative research approach was applied, with a descriptive level of research, documentary and field type, as well as the analytical and synthetic method and techniques such as the student survey, parents and teachers, in addition to the interview with the academic authority of the institution; and for its application, the questionnaire was used as a data collection instrument. The results obtained were processed for the diagnosis of the problem focused on two parts, the diagnosis of the teacher's role in environmental education and the diagnosis of actions for environmental sustainability. It is concluded that the teacher is the main actor in the integral formation of the student, therefore, he must direct his work through the introduction of environmental skills in each of his areas, creating awareness in the students and their families, about the friendly treatment with nature. and the resources it provides us.